Peran Operasi Siber Rusia dalam Perang Rusia-Ukraina dalam Mencapai Tujuan Strategis Rusia. - Firdini, Firdini; Panggabean, Jeffri Urbanus; Anwar, Syaiful (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2024)
Experts predict that there will be a cyber war when Russia invades Ukraine. Russia is expected to use offensive cyberattacks to create surprise and undermine Ukraine's defenses and morale. Cyberattacks are seen as sufficient to achieve Russia's goals without the need for conventional military force. Cyber operations are predicted to provide strategic advantages for Russia, both as a complement to military power and as an independent instrument. This study seeks to assess the impact of cyber operations that accompanied Russia's invasion in the Russia-Ukraine conflict, considering the circumstances and conditions of the situation. The research approach is a qualitative analysis of literature about the Russia-Ukraine conflict. The results show no evidence to support that Russia's cyber operations measurably affect the course of the conflict, provide tactical advantages, or observable strategic value. Cyber operations tend to produce effects that are immeasurable and difficult to control fully. Cyber operations are not a replacement for military force but can complement military operations. They can be effective for data gathering or disruptive operations, especially in gray zone conflicts. Proper planning, preparation, and resource allocation are necessary for successful cyber operations.